MENINGKATKAN KEMAMPUAN DAN KETERAMPILAN SISWA DAKAM MENULIS TEKS CERPEN MELALUI MEDIA PENAMPILAN REKAMAN DAN GAMBAR-GAMBAR ILUSTRASI SEBUAH PERISTIWA DI KELAS XI IPS -3 SMA NEGERI 1 PERBAUNGAN TAHUN PELAJARAN 2019/2020 - Riadi, Riadi (JGK (Jurnal Guru Kita), 2021)
The problem of this research is how the use of recorded media and illustrative images of an event can improve students’ abilities and skills in writing poetry for class XI IPS-3 students of SMA Negeri 1 Perbaungan. This study aims to determine the extent to which the use of recorded performance media and illustrative images of an event can improve the ability and skills in writing poetry for class XI IPS-3 students of SMA Negeri 1 Perbaungan. The research subjects were students of class XI IPS-3 in the odd semester of the 2019/2020 academic year who used instructional media to improve their ability to write poetry. All data listed were obtained through observing student documents and teacher notes. This research was conducted through three cycles, each cycle through the stages of action planning, implementation of action, implementation of observation and reflection. With KM 75. The results of cycles I, II, and III were: 1. In cycle I students were able to achieve KKM on the cognitive aspect of 14 students or 42.40% with an average score of 69.3. And students achieve KKM on poetry writing skills 10 students or 30.3% with an average value of 64.32. In cycle II students were able to achieve KKM on the cognitive aspect of 19 students or 57.60 with an average score of 73.5 And students achieved KKM on short story writing skills of 16 students or 48.5% with an average score of 72.82. In cycle III students were able to achieve KKM on the cognitive aspect of 31 students or 93.95% with an average score of 87.9 And students achieved KKM on short story writing skills 28 students or 84.9% with an average score of 78.27.